CHARACTERIZATION OF ACTIVE CARBON FROM COCONUT SHELL USING X-RAY DIFFRACTION (X-RD) AND SEM-EDX TECHNIQUES - Bakti, Andi Ikhtiar; Gareso, Paulus Lobo; Rauf, Nurlaela (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2018)
Activated carbon is produced from the coconut shell through physical and chemical activation. The pyrolysis method was employed in this research for physical activation at an optimum temperature of 600oC and 1,000oC, for chemical activation immersed using 10% Na2CO3 activating agent. This research has produced two samples, namely the physical activation of 1,000oC and the physics-chemical activation of Na2CO3. The X-Ray Diffraction (X-RD) spectrum of activated carbon in the samples 1,000oC and Na2CO3 contained silicate minerals, iron ore and quartz, respectively, and it showed the formation of carbon and graphite structures in the hkl (002) and (100) planes. Through Scherrer?s method, the average size of the Na2CO3 crystals sample is 15.03 nm and the sample crystal sample of 1,000oC is 54.53 nm; the size of the Nano-scale crystals was formed when the temperature increases ? 600° C. The X-RD resulted the percentage of elemental content carbon phase volume fraction (Fv) and impurity (I) in the 1,000oC sample of 75.61%, 24.39% and the Na2CO3 sample of 77.87%, 22.13% . These results indicate that the carbon content in chemical activation is much better than the physics activation. SEM results with magnification of 5,000x, it is very clear the porosity formed of the 10 ?m picture size are 0.8 ?m in Na2CO3 sample and 1.00 ?m in 1,000oC sample.